Bunbury Basalt: Gondwana breakup products or earliest vestiges of the Kerguelen mantle plume? - Olierook, Hugo; Jourdan, Fred; Merle, R.; Timms, Nicholas Eric; Kusznir, N.; Muhling, Janet (2016)
© 2016 Elsevier B.V. In this contribution, we investigate the role of a mantle plume in the genesis of the Bunbury Basalt using high-precision 40Ar/39Ar geochronology and whole-rock geochemistry, and by using crustal basement thickness of the eastern Indian Ocean and the western Australian continent. The Bunbury Basalt is a series of lava flows and deep intrusive rocks in southwestern Australia thought to be the earliest igneous products from the proto-Kerguelen mantle plume. Nine new plateau ages indicate that the Bunbury Basalt erupted in three distinct phases, at 136.96±0.43 Ma, 132.71±0.43 Ma and 130.45±0.82 Ma. All Bunbury Basalt samples are enriched tholeiitic basalts with varying contributions from the continental lithosphere that are similar to other Kerguelen plume-products. Based on plate reconstructions and the present geochronological constraints, the eruption of the oldest Bunbury Basalt preceded the emplacement of the Kerguelen large igneous province by at least 10-20 m.y. Such age differences between a precursor and the main magmatic event are not uncommon but do require additional explanation. Low crustal stretching factors beneath the Bunbury Basalt (ß˜1.4) indicate that decompression melting could not have been generated from asthenospheric mantle with a normal chemistry and geotherm. An elevated geotherm from the mantle plume coupled with the geochemical similarity between the Bunbury Basalt and other Kerguelen plume-products suggests a shared origin exists. However, new age constraints of the oldest Bunbury Basalt are synchronous with the breakup of eastern Gondwana and the initial opening of the Indian Ocean at ca. 137-136 Ma, which may mean an alternative explanation is possible. The enriched geochemistry can equally be explained by a patch of shallow mantle beneath the southern Perth Basin. The patch may have been enriched during Gondwana suturing at ca. 550-500 Ma, during early rifting events by magmatic underplating or by intruded melts into the subcontinental lithospheric mantle. This enriched geochemical signature would then be sufficient to trigger decompression melting from passive rifting between Greater India and Australia with no contribution from the Kerguelen hotspot. We conclude that although the proto-Kerguelen hotspot is certainly a possible explanation for the genesis of the Bunbury Basalt, decompression melting of an enriched patch of subcontinental lithospheric mantle is an alternative theory.